THE CONSTRUCTION OF CULTURAL EDUCATION IN TETRALOGY OF LASKAR PELANGI NOVEL - Hasan Suaedi; Anang Santoso; Wahyudi Siswanto; Yuni Pratiwi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2019)
A culture needs to be constructed to the members of the community with the aim to inherit a culture, instilling cultural values, and forming good behavior. In order to reveal the construction of cultural education in tetralogy of Laskar Pelangi novel, then a critical discourse analysis study is used. The construction of cultural education in tetralogy of Laskar Pelangi novel was constructed by three figures, namely the knowledgeable, religious, and government figures. In addition, the method of constructing cultural education in tetralogy of Laskar Pelangi novel uses three methods; they are beliefs, customs, and arts.